Value of initial relationships in new business start-ups - Santos, José Novais (2022)
Purpose – Several studies have focussed on new ventures and the development of their first business relationships. However, the understanding of the value functions and involvement in those relationships remain inadequate. The purpose of this paper is to explore the relating process of a new venture by combining the value function framework and the notion of the degrees of involvement in business relationships. Design/methodology/approach – The authors rely on two exploratory longitudinal case studies that focus on two start-ups. In both cases, the evolution of initial relationships with suppliers and customers over a period of time are studied. Findings – The process of relating can occur through a diversity of business relationships manifested in both their value functions and their degree of involvement. The combination of value functions is not stable over time nor is the degree of involvement in business relationships. Moreover, specific interdependencies emerge between the value functions in the customer base and the supplier base of the new ventures over time. Originality/value – This paper is among the few that explore the emergence of new ventures by considering both suppliers and customer relationships. From a business network perspective, the paper also shows that combining value functions and degrees of involvement provides a better understanding of the role of relationship diversity in the process of becoming a node in the business network.